Transmission of Patient Vital Signs using Wireless Body Area Networks - B. Chen; D Pompili (Mobile Networks and Applications (Springer), 2010)
Triage is the process of prioritizing patients based on the severity of their condition when resources are insufficient. Hospitals today are equipped with more and more electronic medical devices. This results in possibly high level of electromagnetic interference that may lead to the failure of medical monitoring devices. Moreover, a patient is usually moved between different hospital settings during triage. Accurate and quick prioritization of patient vital signs under such environment is crucial for making efficient and realtime decisions. In this article, a novel in-network solution to prioritize the transmission of patient vital signs using wireless body area networks is proposed; the solution relies on a distributed priority scheduling strategy based on the current patient condition and on the vital sign end-to-end delay/reliability requirement. The proposed solution was implemented in TinyOS and its performance was tested in a real scenario.